Stauffer syndrome, clinical implications and knowledge gaps, does size matter? case report (2020)
Background: Stauffer Syndrome (SS) is a paraneoplastic disorder associated with renal cell carcinoma (RCC). First described by Herbert Maurice Stauffer in 1961, it is characterized by hepatic dysfunction in the absence of metastasis, and elevated alkaline phosphatase, aminotransferases and prolonged prothrombin time. Initial reports did not include jaundice as an inclusion criterion. We aim to report the rare SS jaundice variant in a patient with a small renal mass and review the literature to determine if the size of the renal mass could influence the development of the SS. Case presentation: The aim of this article is to present the case of a 53-year-old male with Stauffer syndrome jaundice variant secondary to a 2.5 cm renal mass, treated with laparoscopic radical nephrectomy with complete resolution of the syndrome. Conclusions: This syndrome is yet to be fully understood, and as far as the evidence shows, size does not matter. This entity should always be in mind when encountered with a patient with liver dysfunction and jaundice with a suspicion or confirmed diagnosis of a renal mass. To date, and to our knowledge, there have been eleven reported cases of paraneoplastic cholestatic jaundice syndrome including the current case. Six cases presented in patients with small renal mases (< 4 cm), curiously there were not a laterality tendency.